2011
DOI: 10.4238/2011.december.22.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci mapping associated with maize kernel number per ear based on a recombinant inbred line population grown under different nitrogen regimes

Abstract: ABSTRACT. Kernel number per ear (KNE) is one of the most important yield-related agronomic traits in maize (Zea mays). To clarify its genetic basis, we made a quantitative trait locus (QTL) analysis of KNE in a recombinant inbred line population derived from lines Mo17 and Huangzao4, under two nitrogen (N) regimes. Seven QTLs, on chromosomes 4, 6 and 9, were mapped under the high N regime, which explained phenotypic variation ranging from 5.03 to 15.49%. Under the low N regime, three QTLs were located on chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The QTL located in chromosome 6 is especially interesting because it explained a high proportion of the genetic variance (17 %) with the lowest estimation bias for this parameter and with a high detection frequency (95 %) through CV runs. Although no QTL for yield under infestation with corn borers have been previously found in this region (bin 6.01- 6.02) several studies have reported important QTL for grain yield and its components in physiological conditions in the same region in other mapping populations [ 34 38 ]. Even the results of a fine mapping study suggest that a pleiotropic locus could be affecting grain yield and related traits in this region of chromosome 6 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The QTL located in chromosome 6 is especially interesting because it explained a high proportion of the genetic variance (17 %) with the lowest estimation bias for this parameter and with a high detection frequency (95 %) through CV runs. Although no QTL for yield under infestation with corn borers have been previously found in this region (bin 6.01- 6.02) several studies have reported important QTL for grain yield and its components in physiological conditions in the same region in other mapping populations [ 34 38 ]. Even the results of a fine mapping study suggest that a pleiotropic locus could be affecting grain yield and related traits in this region of chromosome 6 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many QTLs for GY-related traits were identified on 6S of the maize chromosome by multiple groups, such as a QTL for ear length (EL) in phi126-bnlg1371 [20], bnlg1538-bnlg391 [21] and phi126-npi235 [1]. Liu et al (2011) identified a QTL for KNPR around phi031 in Y1-umc1257 (6.01–6.02bin) [22], and Tan et al (2011) identified a QTL for kernel weight in umc1656-umc1796 (6.02–6.04bin) [23]. Our group identified a chromosome segment around gpc2 harboring a QTL for KNPR across four environments, designated as qKNPR6 [24].…”
Section: Introductionmentioning
confidence: 99%